The Ability to Memorize the Qur’an: How Does the Effectiveness of the Wahdah and Sima’i Methods? - Syifa Adilla Zahra; Nurul Azizah; Imam Syafe’i; Syaiful Anwar; Erni Yusnita (Yayasan Pendidikan Bima Berilmu, 2025)
The purpose of this study is to assess the effectiveness of the Wahdah and Sima’i methods in enhancing the ability to memorize the Qur'an, as well as to examine the differences in effectiveness between these two methods. This research employs a quantitative approach with a quasi-experimental design. The population in this study consists of eighth-grade students who use the Wahdah method, Sima’i method, and conventional methods.